The effect of shadow training using consecutive steps and cross steps on the agility of the footwork of badminton athletes - Muthiarani, Ahiriah; Lismadiana, Lismadiana; Yuniana, Rina (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2021)
This study aims to determine the effect of sequential and crossed step shadow exercises, as well as the differences between the two on improving footwork agility badminton athlete Â PB Wiratama Jaya Yogyakarta. This research is a quasi-experimental study, with a two group pre-test post-test design. The sample in this study amounted to 22 male athletes. The instrument in this study used a series of foot exercises proposed by Tohar. Data analysis techniques on hypothesis testing using the t test. The results showed: first, there was an effect of sequential step shadow training on the agility of the athlete's footwork PB Wiratama Jaya Yogyakarta with a t value of -4.5 and a calculated significance of 0.001. Second, there is an effect of cross-step shadow training on the agility of the athlete's PB Wiratama Jaya Yogyakarta footwork with a t value of -4.667 and a calculated significance of 0.001. and third, there is no significant difference between sequential step shadow training and cross step shadow training in increasing the agility of the footwork athlete PB Wiratama Jaya Yogyakarta. This is based on data obtained from the t value of -1.353 with a significance of 0.191.